2017
DOI: 10.1080/13603116.2017.1357768
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural empathy among Norwegian students: an inclusive citizenship perspective

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…On the other hand, it is well-known that migrants and children of migrants born and raised in new home countries experience challenges in being recognised as legitimate, equal members of such societies. This rejection often takes the form of ethnic, racial or religious discrimination (Gullestad 2004, Osler and Solhaug 2018. These two dimensions echo insights from academic explorations of belonging, which stress the relational dimension of belonging, whereby selfidentification is not independent of categorization by others (Antonsich 2010).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, it is well-known that migrants and children of migrants born and raised in new home countries experience challenges in being recognised as legitimate, equal members of such societies. This rejection often takes the form of ethnic, racial or religious discrimination (Gullestad 2004, Osler and Solhaug 2018. These two dimensions echo insights from academic explorations of belonging, which stress the relational dimension of belonging, whereby selfidentification is not independent of categorization by others (Antonsich 2010).…”
Section: Introductionmentioning
confidence: 96%
“…This article contributes to the current debate on human rights education in increasingly diverse societies. It does so by focusing on the right to participation, as expressed in article 12 of the Convention on the Rights of the Child (CRC) 1 (Lundy 2007, Osler andSolhaug 2018). The participation of young people in articulating national belonging, including any contestations or assertions linked to this concept, is of critical importance in increasingly diverse societies (Antonsich 2015, Botterill et al 2017, Staeheli and Hammett 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have published our initial findings relating to intercultural empathy among students and the possibilities for inclusive citizenship. Importantly, we found that higher levels of intercultural empathy were moderately associated with students’ perceptions of successful human rights/child rights implementation at their school (Solhaug and Osler, 2018).…”
Section: Student and Teacher Responses To The Measurement Scalementioning
confidence: 92%
“…Atendiendo a ello, se han multiplicado los estudios acerca del enfoque intercultural en la enseñanza de la H, G y CCSS. Algunos de los principales temas de estas investigaciones dicen relación con el desarrollo de la empatía intercultural en la sala de clases y la necesidad de abordar las perspectivas históricas y culturales de los estudiantes inmigrantes en la asignatura de H, G y CCSS (Zembylas & Kambani, 2012;Hawley, Crowe & Mooney, 2016;Ho, McAcoy, Hess & Gibbs, 2017;Solhaug & Osler, 2018, entre muchos otros).…”
Section: Investigaciones Acerca De La Educación Intercultural Y La Enunclassified